Re-engineering humanity / Brett Frischmann, Evan Selinger. - Frischmann, Brett M.; Selinger, Evan, 1974- (Cambridge University Press, 2018)
Every day, new warnings emerge about artificial intelligence rebelling against us. All the while, a more immediate dilemma flies under the radar. Have forces been unleashed that are thrusting humanity down an ill-advised path, one that's increasingly making us behave like simple machines? In this wide-reaching, interdisciplinary book, Brett Frischmann and Evan Selinger examine what's happening to our lives as society embraces big data, predictive analytics, and smart environments. They explain how the goal of designing programmable worlds goes hand in hand with engineering predictable and programmable people. Detailing new frameworks, provocative case studies, and mind-blowing thought experiments, Frischmann and Selinger reveal hidden connections between fitness trackers, electronic contracts, social media platforms, robotic companions, fake news, autonomous cars, and more. This powerful analysis should be read by anyone interested in understanding exactly how technology threatens the future of our society, and what we can do now to build something better.